Business plan and managerial decision changes of small retailers operating in Mykolaiv after the Russian invasion of Ukraine in 2022 - Novytskyi, Volodymyr; Martínez Pantoja, Yadira Ixchel; Průša, Přemysl, 1980-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
This thesis is dedicated to the business plans and managerial decision changes of small retailers operating in Mykolaiv after the Russian invasion of Ukraine in 2022. The notions of business plan and management during a crisis are discussed. The main goal of the thesis is to find out what challenges the war posed on small retailers and how they coped with them. In order to reach the goal of the thesis, seven in-depth interviews with small business owners operating in Mykolaiv were conducted. The research showed that the main challenges were the extreme demand in the first months of the war, delivery disruptions and problems with suppliers, lack of human resources, and changes in macroeconomic factors. Based on the analysis of the findings, recommendations for the owners of small companies in other countries at risk of war have been developed.
Vedoucí práce: Yadira Ixchel Martínez Pantoja
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses